2008
DOI: 10.1088/0953-2048/21/9/095008
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for two distinct scales of current flow in polycrystalline Sm and Nd iron oxypnictides

Abstract: Early studies have found quasi-reversible magnetization curves in polycrystalline bulk rare-earth iron oxypnictides that suggest either wide-spread obstacles to intergranular current or very weak vortex pinning. In the present study of polycrystalline samarium and neodymium rare-earth iron oxypnictide samples made by high pressure synthesis, the hysteretic magnetization is significantly enhanced. Magneto optical imaging and study of the field dependence of the remanent magnetization as a function of particle s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
177
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(202 citation statements)
references
References 51 publications
23
177
2
Order By: Relevance
“…Bulk polycrystalline samples were exposed to many cycles of ever increasing magnetic field H a , followed by removal of the field and measurement of the remanent moment, m R . 11 For a pure, homogeneous sample, we expect flux to penetrate when H a /(1-D) first exceeds the lower critical field H c1 , where D is the relevant demagnetizing factor. For weakly coupled polycrystals, flux penetration occurs preferentially at grain boundaries, pores or nonsuperconducting second phases at lower fields than are needed to penetrate into the grains.…”
Section: Magnetization Measurementsmentioning
confidence: 95%
See 1 more Smart Citation
“…Bulk polycrystalline samples were exposed to many cycles of ever increasing magnetic field H a , followed by removal of the field and measurement of the remanent moment, m R . 11 For a pure, homogeneous sample, we expect flux to penetrate when H a /(1-D) first exceeds the lower critical field H c1 , where D is the relevant demagnetizing factor. For weakly coupled polycrystals, flux penetration occurs preferentially at grain boundaries, pores or nonsuperconducting second phases at lower fields than are needed to penetrate into the grains.…”
Section: Magnetization Measurementsmentioning
confidence: 95%
“…11,13,14,15,16,17 In our previous study, evidence for two distinct scales of current flow was found in polycrystalline Sm-and Nd -1111 samples using magneto-optical imaging (MO) and analysis of the field dependence of the remanent magnetization (RM). 11 A global current density J c global flowing in the whole sample of order 4000 A/cm 2 was determined at 4 K in self-field. This value, which appears to be more than one order of magnitude larger than for early results on randomly-oriented polycrystalline cuprates, 18 is still one of the highest for polycrystalline pnictides reported to date.…”
Section: Introductionmentioning
confidence: 97%
“…The discovery of superconductivity in the LaFeAsO 1-x F x compound [1] has been followed by rapid exploration of many aspects of the superconducting behaviour of the broad class of rare earth iron oxypnictides [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] whose transition temperature T c can reach above 40 K when La is replaced by Ce [5] and above 50 K when the rare earth is Pr, Nd, Sm and Gd [7][8][9][10][11]. Hunte et al reported that even the La Fe-oxypnictide with Tc ~ 26 K exhibits a very high upper critical field H c2 of ~65 T [6] while H c2 over 200 T was deduced for the Sm and Nd Fe-oxypnictides [17], strongly suggesting a large high field domain for the Fe-oxypnictides.…”
Section: Introductionmentioning
confidence: 99%
“…Foreseeing practical applications, there has been immediate interest in the critical current density too. But all polycrystalline samples of La, Sm and Nd Fe-oxypnictides [12][13][14][15][16] examined to date show signs of less than full grain-to-grain connectivity, raising the same concern of depression of superconducting order parameter at grain boundaries that has so greatly complicated applications of the cuprates [18]. Grain boundary order parameter suppression is fundamental detriment to applications since it means that a randomly aligned grain structure will not pass the full current that can be sustained by intragrain vortex pinning, thus reducing the global or whole-sample current density below that circulating in the grains.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, many workers have focused on magnetic and transport properties of the series [10][11][12][13][14][15][16][17]. Detailed phase diagram and transport properties of SmFeAsO 1-x F x were studied, and it was found that superconductivity emerges at x=0.10 and optimal doping takes place at x=0.2 with the highest Tc=54 K [10].…”
Section: Introductionmentioning
confidence: 99%